find the value of a for which the zero of the polynomial x2 - 6x + a satisfy the relation 3 alpha + 2 beeta = 20
Answers
Answered by
6
Given: alpha and beta are the zeroes of given p(x)= x²-6x+a
we know that,
◎sum of zeroes= -b/a
![\alpha + \beta = 6 \alpha + \beta = 6](https://tex.z-dn.net/?f=+%5Calpha++%2B++%5Cbeta++%3D+6)
———————————————(1)
also,
◎product of zeroes= c/a
![\alpha \beta = a \alpha \beta = a](https://tex.z-dn.net/?f=+%5Calpha++%5Cbeta++%3D+a)
—————————————————(2)
now,
![3 \alpha + 2 \beta = 20 \: \: \: \: \: (given) 3 \alpha + 2 \beta = 20 \: \: \: \: \: (given)](https://tex.z-dn.net/?f=3+%5Calpha++%2B+2+%5Cbeta++%3D+20+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+%28given%29)
——————————————————(3)
◎ multiply 2 to equation (1) and subtract (1) from (2)
![3 \alpha + 2 \beta = 20 \\ 2 \alpha + 2 \beta = 12 \\ ...................... \\ \: \: \alpha \: \: \: \: \: = 8 \\ ...................... 3 \alpha + 2 \beta = 20 \\ 2 \alpha + 2 \beta = 12 \\ ...................... \\ \: \: \alpha \: \: \: \: \: = 8 \\ ......................](https://tex.z-dn.net/?f=3+%5Calpha++%2B+2+%5Cbeta++%3D+20+%5C%5C+2+%5Calpha++%2B+2+%5Cbeta++%3D+12+%5C%5C+......................+%5C%5C+++%5C%3A++%5C%3A+%5Calpha++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%3D+8+%5C%5C+......................)
put this value in (1)
![8 + \beta = 6 \\ \\ \beta = - 2 8 + \beta = 6 \\ \\ \beta = - 2](https://tex.z-dn.net/?f=8+%2B++%5Cbeta++%3D+6+%5C%5C++%5C%5C++%5Cbeta++%3D++-+2)
![substitute \: the \: value \: of \: \\ \alpha \: and \: \beta \: in \: (2) substitute \: the \: value \: of \: \\ \alpha \: and \: \beta \: in \: (2)](https://tex.z-dn.net/?f=substitute+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A++%5C%5C++%5Calpha++%5C%3A+and+%5C%3A++%5Cbeta++%5C%3A+in+%5C%3A+%282%29)
![a = \alpha \beta \\ \\ a = 8 \times - 2 \\ \\ a = - 16 a = \alpha \beta \\ \\ a = 8 \times - 2 \\ \\ a = - 16](https://tex.z-dn.net/?f=a+%3D++%5Calpha++%5Cbeta++%5C%5C++%5C%5C+a+%3D+8+%5Ctimes++-+2+%5C%5C++%5C%5C+a+%3D++-+16)
we know that,
◎sum of zeroes= -b/a
———————————————(1)
also,
◎product of zeroes= c/a
—————————————————(2)
now,
——————————————————(3)
◎ multiply 2 to equation (1) and subtract (1) from (2)
put this value in (1)
Answered by
0
Answer:
please inbox me
Step-by-step explanation:
Sorry I didn't know the answer
Similar questions